Digital twinning of river basins towards full-scale, sustainable and equitable water management and disaster mitigation - Yifan Yang; Chen Xie; Ziwu Fan; Zhonghou Xu; Bruce W. Melville; Guoqing Liu; Lei Hong (npj Natural Hazards)
Abstract Digital twins are transforming the paradigm of water management and water hazard mitigation globally, facilitating more effective governance. However, comprehensive digitalisation at the basin scale still faces major challenges in data, modelling, policy incentives, and, most critically, widespread inequity. This article outlines a framework for building widely applicable digital-twin basins and addressing the main obstacles. Ensuring high-quality water data requires more comprehensive and well-controlled data aggregation and provision protocols. Significant improvements to the existing data infrastructure are necessary to support this effort. Most existing water models are not effectively integrated and do not include multi-physics to reflect all essential correlated physical processes at the basin scale. The current advancement in physics-informed data-driven approaches may provide a solution. Furthermore, global initiatives are critical to reducing major inequity in less developed regions, particularly the Global South, during digitalisation. It is imperative that researchers, practitioners and policymakers take decisive actions to prioritise research and allocate resources to foster transboundary collaborations towards integrated and extensive digital-twin basin systems, promoting the sustainability and resilience of global water resources.